2021
DOI: 10.1038/s43246-021-00118-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of cell cryopreservation with polyampholytes studied by solid-state NMR

Abstract: Polyampholytes are emerging macromolecular membrane non-penetrating cryoprotectants; however, the mechanism behind their cryopreservation remains unclear. Here, we investigated the mechanism using solid-state NMR spectroscopy. The polymer-chain dynamics and the water and ion mobilities in the presence of various membrane penetrating and non-penetrating cryoprotectants were monitored at low temperatures to mimic cryopreservation conditions. NMR experiments revealed that the water, Sodium-ion, and polymer-chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 69 publications
0
70
0
Order By: Relevance
“…This result supports the transition from DMSO to non-DMSO in order to enable scale-up of the fill-and-finish process in a manufacturing setting, while adhering to a high batch consistency. Compared with DMSO whose cytotoxicity arises from dissolution, epigenetic and genomic alteration, these non-DMSO CPAs, typically with larger molecular weight than DMSO, can cause pre-freeze cell loss predominantly due to osmotic stress upon CPA introduction ( Best, 2015 ; Hornberger et al, 2021 ; Matsumura et al, 2021 ). Compared with D5 crest and D7 SN, which exhibited no significant cell loss over the course of prefreeze exposure to the non-DMSO CPA solution ( p > 0.05), D14 mSN experienced minor (10%) yet significant ( p < 0.05) decrease in viable cell count during the first 30 min of this process, suggesting that sensitivity to the osmotic stress varied by cell stage with the most mature cells being most sensitive.…”
Section: Discussionmentioning
confidence: 99%
“…This result supports the transition from DMSO to non-DMSO in order to enable scale-up of the fill-and-finish process in a manufacturing setting, while adhering to a high batch consistency. Compared with DMSO whose cytotoxicity arises from dissolution, epigenetic and genomic alteration, these non-DMSO CPAs, typically with larger molecular weight than DMSO, can cause pre-freeze cell loss predominantly due to osmotic stress upon CPA introduction ( Best, 2015 ; Hornberger et al, 2021 ; Matsumura et al, 2021 ). Compared with D5 crest and D7 SN, which exhibited no significant cell loss over the course of prefreeze exposure to the non-DMSO CPA solution ( p > 0.05), D14 mSN experienced minor (10%) yet significant ( p < 0.05) decrease in viable cell count during the first 30 min of this process, suggesting that sensitivity to the osmotic stress varied by cell stage with the most mature cells being most sensitive.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a novel cryoprotectant, carboxylated poly-L-lysine, was examined and found to indicate restricted mobility and increased solution viscosity of eukaryotic cells. In addition, intermolecular interactions facilitated the glass transition of carboxylated poly-L-lysine, which prevents intracellular ice formation and osmotic shock during freezing [88].…”
Section: Cryoprotectantsmentioning
confidence: 99%
“…Although mechanistic studies using synthetic polyampholytes suggested that they protect the cell membrane from freezing-induced damages [ 21 ], a conclusive mechanism was unknown. In this study, we show molecular-level investigation of the mechanism of cryopreservation using solid-state NMR [ 22 ]. We investigated the soluble state as well as the molecular mobilities of the polymer chain, water, and salts at freezing temperatures and compared it with control samples to demonstrate polyampholytes’ ability to prevent dehydration and decrease intracellular ice freezing during cryopreservation.…”
Section: Polyampholytes For Low-temperature Preservation Of Cells and Proteinsmentioning
confidence: 99%